A viral protein disrupts vacuolar acidification to facilitate virus infection in plants. (9th December 2021) - Yang, Meng; Ismayil, Asigul; Jiang, Zhihao; Wang, Yan; Zheng, Xiyin; Yan, Liming; Hong, Yiguo; Li, Dawei; Liu, Yule
Abstract: Vacuolar acidification is essential for vacuoles in diverse physiological functions. However, its role in plant defense, and whether and how pathogens affect vacuolar acidification to promote infection remain unknown. Here, we show that Barley stripe mosaic virus (BSMV) replicase γa, but not its mutant γaR569A, directly blocks acidification of vacuolar lumen and suppresses autophagic degradation to promote viral infection in plants. These were achieved via molecular interaction between γa and V‐ATPase catalytic subunit B2 (VHA‐B2), leading to disruption of the interaction between VHA‐B2 and V‐ATPase catalytic subunit E (VHA‐E), which impairs the membrane localization of VHA‐B2 and suppresses V‐ATPase activity. Furthermore, a mutant virus BSMVR569A with the R569A point mutation possesses less viral pathogenicity. Interestingly, multiple viral infections block vacuolar acidification. These findings reveal that functional vacuolar acidification is required for plant antiviral defense and disruption of vacuolar acidification could be a general viral counter‐defense strategy employed by multiple viruses. Synopsis: A viral protein inhibits vacuolar acidification to facilitate viral infection by suppressing vacuolar H + ‐ATPase activity via its interaction with the V‐ATPase subunit B2. Barley stripe mosaic virus (BSMV) γa protein blocks the acidification of vacuoles and the degradation of autophagic bodies. BSMV γa directly interacts with host vacuolar H + ‐ATPase subunit B2 (VHA‐B2) to competitively disrupt the VHA‐B2‐VHA‐E interaction in plants. BSMV γa partially changes the subcellular localization of VHA‐B2 from membrane to cytosol and suppresses V‐ATPase activity. Disruption of vacuolar acidification could be a general viral counter‐defense strategy employed by multiple viruses Abstract : A viral protein disrupts vacuolar acidification to facilitate virus infection in plants.